(untitled) (International Journal of Engineering and Computer Science, 2016)
The security of Transmission of data becomes a huge issue in information and communication Technology. So ,to ensure the security of data during transmission, Two major techniques are adopted. They are Cryptography and Steganography. In these, the input data is encrypted using encryption algorithms and embedded into carrier image then transmitted through a communication channel, at the receiver side, data decrypted using data decryption algorithms is restored with error free. We are conducting a survey in this paper based on different steganographic and cryptographic methods for Data security.